$b^2=ac\Rightarrow \dfrac ab = \dfrac bc\\c^2=bd\Rightarrow \dfrac bc = \dfrac cd\\\Rightarrow \dfrac ab=\dfrac bc=\dfrac cd\\\Rightarrow \dfrac ab=\dfrac bc=\dfrac cd=\dfrac{a+b-c}{b+c-d}\\\Rightarrow \left ( \dfrac ab \right )^3=\left ( \dfrac bc \right )^3=\left ( \dfrac cd \right )^3=\left ( \dfrac{a+b-c}{b+c-d} \right )^3\\\Rightarrow \dfrac{(a+b-c)^3}{(b+c-d)^3}=\dfrac{a^3}{b^3}=\dfrac{b^3}{c^3}=\dfrac{c^3}{d^3}=\dfrac{a^3+b^3-c^3}{b^3+c^3-d^3}$
$\dfrac{a+b}{a-b}=\dfrac{c+a}{c-a}\\\Rightarrow (a+b)(c-a)=(c+a)(a-b)\\\Rightarrow c(a+b)-a(a+b)=c(a-b)+a(a-b)\\\Rightarrow ac+bc-a^2-ab=ac-bc+a^2-ab\\\Rightarrow 2bc=2a^2\\\Rightarrow bc=a^2\\\Rightarrow \dfrac ba=\dfrac ac$